GEOMOPHOLOGICAL CHARACTERISTICS AND ENVIRONMENTAL SENSITIVITY INDEX FOR OIL SPILLS OF ANAVYSSOS BAY, ATTICA - Kourliaftis, G.; Kapsimalis, V.; Vandarakis, D.; Pavlopoulos, K. (Bulletin of the Geological Society of Greece, 2016)
The study of the coastal and shallow marine geomorphology of the adjacent bays of Anavyssos and Aghios Nikolaos (southeastern Attica) was carried out by acoustic scanning of the seafloor with an echo sounder and sonar side scan; topographical sections perpendicular to the shoreline, collection and analysis of surface sediments; determination of long-term shoreline displacements by comparing old and modern aerial photographs and satellite imagery. The terrestrial part of the coastal area consists of many landforms, such as lagoons, cliffs, beachrocks, tombola etc. The beaches affected by intense human activity have gentle slopes, low elevations and a coarse-grained texture. The remote sensing analysis showed that, over the last six decades, there are some small shoreline changes of the order of ± 2 meters. The bays have relatively gentle gradients covered by sand in their shallower parts and patches of Posidonia Oceanica towards the open sea. Taken into account the texture of sediments and landforms that make up the terrestrial part of the coasts, four categories (1st, 2nd, 3rd and 5th) of Environmental Sensitivity Index for oil spill (ESI) have been identified and an ESI map is created serving as a quick reference for oil spill responders and coastal zone managers.